Intrapreneurship and firm entrepreneurial orientation: insights from the health care service industry - Lages, M.; Marques, C.; Ferreira, J.; Ferreira, F. (International Entrepreneurship and Management Journal, 2017)
Intrapreneurship affects our daily lives and is a research topic of great importance. Given the current economic climate, its relevance to firm performance has increased considerably both among academics and practitioners. Specifically, our approach has focused on the identification, analysis and explanation of the determinants/variables that influence the intrapreneurship process in the health care service industry, including the private, public and social sectors. The methodology employed consisted of collecting primary data via a questionnaire survey. The questionnaire was sent by e-mail to health care employees and middle managers from the northern and center regions of Portugal, and the study covered 202 professionals from 45 organizations. The results show that the participating health care team members present intrapreneurial behavior, and health care organizations create favorable internal conditions that support the theoretical concepts of intrapreneurship and firm entrepreneurial orientation (FEO).